Increasing autophagy and blocking Nrf2 suppress laminopathy‐induced age‐dependent cardiac dysfunction and shortened lifespan. Issue 3 (25th March 2018) - Bhide, Shruti; Trujillo, Adriana S.; O'Connor, Maureen T.; Young, Grant H.; Cryderman, Diane E.; Chandran, Sahaana; Nikravesh, Mastaneh; Wallrath, Lori L.; Melkani, Girish C.
Summary: Mutations in the human LMNA gene cause a collection of diseases known as laminopathies. These include myocardial diseases that exhibit age‐dependent penetrance of dysrhythmias and heart failure. The LMNA gene encodes A‐type lamins, intermediate filaments that support nuclear structure and organize the genome. Mechanisms by which mutant lamins cause age‐dependent heart defects are not well understood. To address this issue, we modeled human disease‐causing mutations in the Drosophila melanogaster Lamin C gene and expressed mutant Lamin C exclusively in the heart. This resulted in progressive cardiac dysfunction, loss of adipose tissue homeostasis, and a shortened adult lifespan. Within cardiac cells, mutant Lamin C aggregated in the cytoplasm, the CncC(Nrf2)/Keap1 redox sensing pathway was activated, mitochondria exhibited abnormal morphology, and the autophagy cargo receptor Ref2(P)/p62 was upregulated. Genetic analyses demonstrated that simultaneous over‐expression of the autophagy kinase Atg1 gene and an RNAi against CncC eliminated the cytoplasmic protein aggregates, restored cardiac function, and lengthened lifespan. These data suggest that simultaneously increasing rates of autophagy and blocking the Nrf2/Keap1 pathway are a potential therapeutic strategy for cardiac laminopathies.